PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS MULTIMEDIA - Arwani, Agus (Forum Tarbiyah, 2011)
In this era of globalization, as at present, consciously orunconsciously, the influence of technology based media is consideredprogressively, by the existence of masses of information channelsin various forms of media. The media has affected all aspects ofour lives, notwithstanding in different degrees. The development ofthe computer world has reached a very impressive development. Itis proved that practically, all occupations in the world have been controlledby computer. Just like other fields, computers are also veryclosely related to education. In the field of teaching, the computerallows for the implementation of distance teaching and learning, orlearning without confronting each other. However, the arised problemsare not as easy as imagined. For example, in this case, teacherswho master the subject matter, mainly are not able to present formsof learning in a computer, while computer experts who are able torealize all the things in the computer, they usually does not masterthe subject matter. We need a software that can help teachers conveytheir ideas into the computer. A multimedia-based teaching mediathat can help teachers deliver the subject matter under their controlthrough the computer is required, therefore independent learningor distance learning can be established.